Development and Control of a Camless Engine Valvetrain. Issue 5 (2019) - Dimitrova, Zlatina; Tari, Massinissa; Lanusse, Patrick; Aioun, François; Moreau, Xavier
Abstract: This paper presents an innovative application of an electromagnetic actuator for a future camless engine valvetrain. The actuators are designed for small gasoline engine. The design method is inversed to create a control-oriented model. The control architecture is designed for a robust control of the actuator. An experimental test bench is built for the correlation of the control model with experimental measures. Control strategies are developed and the performance indicators of the actuators are evaluated. The robust controller method uses CRONE system design methodology. The investigations show that the design of the innovative actuator and of its controller provide very good dynamic performances.